AUTOMATIC FISHPOND IRRIGATION DOOR CONTROL SYSTEM BASED ON ATMEGA16 MICROCONTROLLER AND SMS GATEWAY - B, Muhammad Fajar; Lestary, Fitriyanty Dwi; M. Miftach Fakhri; Muhammad Agung; Surianto, Dewi Fatmarani; Akmal Hidayat (Informatika, Universitas Jenderal Soedirman, 2023)
The process of controlling irrigation doors in fishponds is still mostly done manually, this results in the performance of farmers being less effective and efficient. Current technological developments, especially in the field of IoT, can be used to design a simulation that is able to control irrigation gates automatically. Based on the results of the tests that have been carried out, it can be concluded that the ATmega16-based automatic irrigation gate simulation tool can work well according to the designed working principle. If the condition of fishpond water is less than the ideal height of the fishpond and the condition of river water is more than the height of the fishpond, the motor will move to